2016
DOI: 10.4236/aim.2016.64033
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <i>Listeria monocytogenes</i> in Foods and Characterization by PFGE

Abstract: The aims of the present study were to investigate the prevalence of Listeria monocytogenes in 1042 foods collected from different market to characterize the isolates by phenotypical and molecular methods. In particular, L. monocytogenes obtained from different types of foods such as RTE (kimbap), fish (smoked salmon and seasoned-dried slice fish) and meat (cut raw beef and pork) from 2009 to 2011, were used. Twelve samples (2.1%) were positive for L. monocytogenes. Detection rate of L. monocytogenes varied sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(30 reference statements)
2
6
0
Order By: Relevance
“…The lowest prevalence to our knowledge was 0.8% from a study conducted in South Korea33. Regarding to the raw red meat, the prevalence rate of L. monocytogenes in this study was close to what was found in France (5.0%) and South Korea (5.2%), which support our results 22,34 . In different studies conducted in the Kurdistan region/ Iraq, a higher prevalence was reported from red meat at 14% 17 .…”
Section: Results and Discussion Prevalence Of L Monocytogenes In Difsupporting
confidence: 91%
See 1 more Smart Citation
“…The lowest prevalence to our knowledge was 0.8% from a study conducted in South Korea33. Regarding to the raw red meat, the prevalence rate of L. monocytogenes in this study was close to what was found in France (5.0%) and South Korea (5.2%), which support our results 22,34 . In different studies conducted in the Kurdistan region/ Iraq, a higher prevalence was reported from red meat at 14% 17 .…”
Section: Results and Discussion Prevalence Of L Monocytogenes In Difsupporting
confidence: 91%
“…The purity and the concentration of the DNA was evaluated using Nanodrop (Thermofisher, UK) through the calculation of optical densities ratio at 260/280 nm. L. monocytogenes isolates were confirmed using PCR primers complementary to the highly conserved 16S rRNA sequence as stated by 22 . The reaction conditions consisted of initial denaturation of DNA template (94°C for 3 min), then 35 cycles of denaturation (94°C for 1 min), annealing (60°C for 2 min) and extension (72°C for 1min).…”
Section: Dna Extraction and Confirmation Of L Monocytogenes Isolatesmentioning
confidence: 99%
“…The bacteria to be tested are cultured, harvested, and cells are washed in isotonic solution to maintain their integrity and then mixed with a low gelling temperature agarose (Lopez-Canovas et al, 2019). The cells-agarose mix is applied to suitable mold plugs, then the bacterial cells are lysed to re- SmaI, ApaI and NotI (Buchrieser et al, 1993;Jang et al, 2005;Park et al, 2016). Several other factors such as electric field strength, field angle and shape, agarose type and concentration, pulse time, ionic strength, and temperature have an influence on the obtained DNA pattern (Jang et al, 2005;Park et al, 2016).…”
Section: Pulsed-field Gel Electrophoresis (Pfge)mentioning
confidence: 99%
“…Isolation of genomic DNA from bacterial colonies was carried out using the boiling method according to the protocol described by (Adzitey et al, 2013;Dashti et al, 2009). 16S rRNA gene primer was described by (Park et al, 2016). The amplification reactions were accomplished in 25μl volume and 100 bp DNA ladder (GeNet Bio, South Korea) was used as a size marker (M) in all gels.…”
Section: Molecular Investigationmentioning
confidence: 99%
“…The amplification reactions were accomplished in 25μl volume and 100 bp DNA ladder (GeNet Bio, South Korea) was used as a size marker (M) in all gels. The amplified DNA bands were separated by using agarose gel electrophoresis as designated by (Park et al, 2016).…”
Section: Molecular Investigationmentioning
confidence: 99%